Methods for Increasing the Number of Experimental Points on a D-Optimal Design (2014)
The purpose of the optimum designs is to determine the optimal experimental conditions in terms of minimum variance of the estimated vector of parameters, so that statistical inferences can be generated as accurate as possible. This theory presupposes kno